2018
DOI: 10.1055/s-0038-1668128
|View full text |Cite
|
Sign up to set email alerts
|

Nonsurgical Treatment of Chest Wall Deformities: Contradiction or Complement?

Abstract: For decades, open surgical repair was the only available method to treat congenital and acquired chest wall deformities (CWDs). In 1998, D. Nuss described a minimally invasive procedure for surgical repair of pectus excavatum (PE), and a few years later H. Abramson reported on his experience with the "reversed Nuss technique" for surgical repair of pectus carinatum (PC). Both procedures are performed with increasing frequency worldwide.However, nonsurgical measures such as vacuum bell (VB) therapy for conserva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…While different treatment techniques have been described in the past, minimally invasive repair of pectus excavatum (MIRPE) developed by Dr. D. Nuss in 1987 and subsequently presented at the American Pediatric Surgery Association Congress in 1997, presently reflects the standard therapy for PE [9,10]. In mild to moderate cases and/or in patients reluctant to operative therapy, vacuum bell (VB) therapy reflects an alternative treatment option to surgery [8,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…While different treatment techniques have been described in the past, minimally invasive repair of pectus excavatum (MIRPE) developed by Dr. D. Nuss in 1987 and subsequently presented at the American Pediatric Surgery Association Congress in 1997, presently reflects the standard therapy for PE [9,10]. In mild to moderate cases and/or in patients reluctant to operative therapy, vacuum bell (VB) therapy reflects an alternative treatment option to surgery [8,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies, in fact, reported an increasing number of patients treated with VB therapy [7], and in 2011, the first systematic retrospective study summarized the results for 133 patients [8]. Recent reports confirmed the efficacy of VB therapy in selected patients [9][10][11][12][13], and larger studies were reported that considered both adult and pediatric patients [14,15].…”
Section: Introductionmentioning
confidence: 99%